2018
DOI: 10.1002/biot.201800364
|View full text |Cite
|
Sign up to set email alerts
|

Pentose Metabolism in Saccharomyces cerevisiae: The Need to Engineer Global Regulatory Systems

Abstract: Extending the host substrate range of industrially relevant microbes, such as Saccharomyces cerevisiae, has been a highly-active area of research since the conception of metabolic engineering. Yet, rational strategies that enable non-native substrate utilization in this yeast without the need for combinatorial and/or evolutionary techniques are underdeveloped. Herein, this review focuses on pentose metabolism in S. cerevisiae as a case study to highlight the challenges in this field. In the last three decades,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 130 publications
2
25
0
Order By: Relevance
“…Conventional D-glucose transporters (Gal2p, Hxt5p, and Hxt7p) from S. cerevisiae can assimilate D-xylose/L-arabinose when D-glucose is not present. However, in lignocellulolytic hydrolysate, the sequential assimilation of sugar, being the pentoses assimilated after D-glucose, characterizes a diauxic growth pattern [8] that would require additional time for reorganization of the metabolic machinery of the yeast to assimilate pentose after consumption of D-glucose (additional lag phase). Furthermore, according to the total sugar concentration in the medium, pentose consumption would be intensified in a culture medium in which fermentative products, such as ethanol and acetic acid, may reduce the kinetics of yeast growth [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conventional D-glucose transporters (Gal2p, Hxt5p, and Hxt7p) from S. cerevisiae can assimilate D-xylose/L-arabinose when D-glucose is not present. However, in lignocellulolytic hydrolysate, the sequential assimilation of sugar, being the pentoses assimilated after D-glucose, characterizes a diauxic growth pattern [8] that would require additional time for reorganization of the metabolic machinery of the yeast to assimilate pentose after consumption of D-glucose (additional lag phase). Furthermore, according to the total sugar concentration in the medium, pentose consumption would be intensified in a culture medium in which fermentative products, such as ethanol and acetic acid, may reduce the kinetics of yeast growth [17].…”
Section: Discussionmentioning
confidence: 99%
“…The global production of lignocellulosic biomass is estimated to be approximately 3-5 gigatons per year [6,7]. However, from the large contingent of hemicelluloses, little is used in fermentative processes, mostly due to the inability of wild-type Saccharomyces cerevisiae to efficiently co-utilize hexoses and pentoses [5,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When recombinant yeast cells able to assimilate xylose were analysed, the results indicated that intracellular xylose triggers a signal similar to carbon starvation in cells that are actively metabolizing xylose, probably causing the low assimilation rates observed with this carbon source (Osiro et al, ). Thus, the mechanisms by which xylose triggers a signalling response in S. cerevisiae are still not clear, and further analyses are required with evidence pointing to the need for a more system‐level rewiring of transcription factors, signalling pathways, and regulatory and structural proteins to achieve efficient pentose assimilation by S. cerevisiae (Endalur‐Gopinarayanan & Nair, ).…”
Section: Transcriptome Analysis Of Nonrecombinant Xylose‐utilizing Smentioning
confidence: 99%